Bi-allelic NRXN1α deletion in microglia derived from iPSC of an autistic patient increases interleukin-6 production and impairs supporting function on neuronal networking - Bose, Raj; Posada-Pérez, Mercedes; Karvela, Eleni; Skandik, Martin; Keane, Lily; Falk, Anna; Spulber, Stefan; Joseph, Bertrand; Ceccatelli, Sandra (Brain, behavior, and immunity, 2025)
•The contributions of neurons and microglia in mediating the effects of gene alterations can be assessed using an iPSC-based platform.•Microglia, as neurons, express the NRXN1 gene encoding for Neurexin-1.•NRXN1 deletion in microglia leads to microglia activation and release of IL6, a pro-inflammatory interleukin associated to ASD.•Microglia bearing an ASD-associated NRXN1-deletion lose the ability to support the formation of functional neuronal networks. Autism spectrum disorder (ASD) is a set of heterogeneous neurodevelopmental conditions, with a highly diverse genetic hereditary component, including altered neuronal circuits, that has an impact on communication skills and behaviours of the affected individuals. Beside the recognised role of neuronal alterations, perturbations of microglia and the associated neuroinflammatory processes have emerged as credible contributors to aetiology and physiopathology of ASD. Mutations in NRXN1, a member of the neurexin family of cell-surface receptors that bind neuroligin, have been associated to ASD. NRXN1 is known to be expressed by neurons where it facilitates synaptic contacts, but it has also been identified in glial cells including microglia. Asserting the impact of ASD-related genes on neuronal versus microglia functions has been challenging. Here, we present an ASD subject-derived induced pluripotent stem cells (iPSC)-based in vitro system to characterise the effects of the ASD-associated NRXN1 gene deletion on neurons and microglia, as well as on the ability of microglia to support neuronal circuit formation and function. Using this approach, we demonstrated that NRXN1 deletion, impacting on the expression of the alpha isoform (NRXN1α), in microglia leads to microglial alterations and release of IL6, a pro-inflammatory interleukin associated with ASD. Moreover, microglia bearing the NRXN1α-deletion, lost the ability to support the formation of functional neuronal networks. The use of recombinant IL6 protein on control microglia-neuron co-cultures or neutralizing antibody to IL6 on their NRXN1α-deficient counterparts, supported a direct contribution of IL6 to the observed neuronal phenotype. Altogether, our data suggest that, in addition to neurons, microglia are also negatively affected by NRXN1α-deletion, and this significantly contributes to the observed neuronal circuit aberrations.